Hand Gesture Control System for Robotic Hand Using Computer Vision (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Human–machine interction plays an important role in modern industrial automation systems. In many industrial environments, operators are required to interact directly with machines through switches, buttons, and control panels. In hazardous environments such as chemical plants, radioactive facilities, and high-voltage power stations, this direct interaction may expose operators to serious safety risks. This paper presents a computer vision–based hand gesture control system that enables contactless interaction with machines. The proposed system uses a camera to capture hand gestures, which are processed using Python with OpenCV and MediaPipe libraries. The system detects hand landmarks and interprets gestures in real time. The recognized gesture is converted into control signals and transmitted to an Arduino microcontroller through serial communication. The Arduino generates PWM signals to control servo motors connected to a robotic hand mechanism that replicates the user’s gesture. The developed prototype demonstrates the feasibility of integrating artificial intelligence and embedded systems for safer human–machine interaction in industrial environments.